An epidemiologic investigation of wastage and productivity of ewes in a sample of New Zealand commercial flocks : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Palmerston North, New Zealand - Griffiths, Kate Jade (Massey University, 2020)
Until recently, little was known about ewe wastage in commercial New Zealand ewe flocks, or indeed, internationally. This PhD was undertaken with the broad objective of establishing the extent, timing and cause (premature culling or mortality) of ewe wastage in New Zealand ewe flocks, while also identifying factors associated with increased ewe wastage including pre-mating body condition score (BCS), failure to rear a lamb and, linked with the latter, impact of ewe udder defects on productivity. To the authors’ knowledge, this is the first study that reports both lifetime wastage and detailed annual wastage in a sample of New Zealand commercial flocks. Of the 13,142 enrolled ewes, 50.4% exited their respective flocks due to premature culling (where a ewe is culled from the flock prior to the potential end of her productive lifespan) and 40.0% due to on-farm dead/missing, giving a total of 90.4% that exited due to wastage. In all years, pre-mating BCS could be used as a predictor of ewe wastage with odds of wastage lower with increasing BCS. In Year 1, wastage for each cohort ranged from 7.6% - 45.4% of ewe lambs enrolled, while wastage due to dead/missing accounted for 26.8% - 100.0% of ewe lamb wastage across cohorts, and premature culling was primarily due to poor reproductive performance (dry at pregnancy diagnosis or dry at docking when 3-6-week-old lambs are yarded for ear marking, tail removal and castration of males). Hence, other than the cull sale-value for those that were prematurely culled, the farmer received no productive or economic benefit from these wasted ewe lambs. Ewe lambs with heavier conceptus adjusted liveweight (CALW) and those that gained greater CALW between pregnancy diagnosis and pre-lambing were less likely to be dry at docking. Similarly, for two-tooth ewes (18-months of age at breeding), heavier ewes and those that gained CALW were less likely to be dry at docking than lighter ewes or those that lost CALW. Pre-mating udder palpation scores of hard or lump were associated with increased odds of lambs not surviving to weaning compared with normal scores. Additionally, surviving offspring of ewes with pre-mating udder palpation scores of hard had lower growth to weaning. Commercial farmers can use the information presented in this thesis to identify ewes within their flocks that have increased risk of wastage or poor productivity. They can then alter management of these at-risk ewes to both improve ewe productivity and reduce likelihood of wastage.
Material in this thesis has been published as: K.J.Griffiths, AL Ridler, C Heuer, RA Corner-Thomas & PR Kenyon. (2016, Dec). The effect of liveweight and body condition score on the ability of ewe lambs to successfully rear their offspring. Small Ruminant Research, 145, 130-135. https://doi.org/10.1016/j.smallrumres.2016.11.001 KJ Griffiths, AL Ridler, C Heuer, RA Corner-Thomas & PR Kenyon. (2018). Associations between liveweight, body condition score and previous reproductive outcomes, andthe risk of ewes bred at 18-months of age being dry at docking, New Zealand Veterinary Journal, 66(6), 290-296. https://doi.org/10.1080/00480169.2018.1498035 KJ Griffiths, AL Ridler, CWR Compton, RA Corner-Thomas & PR Kenyon. (2019.) Investigating associations between lamb survival to weaning and dam udder and teatscores, New Zealand Veterinary Journal, 67(4), 163-171. https://doi.org/10.1080/00480169.2019.1596523 KJ Griffiths, AL Ridler, CWR Compton, RA Corner-Thomas & PR Kenyon. (2019). Associations between lamb growth to weaning and dam udder and teat scores, New Zealand Veterinary Journal, 67(4), 172-179. https://doi.org/10.1080/00480169.2019.1596524
Keywords: Ewes; Losses; Productivity; New Zealand; Sheep farming; 300905 Veterinary epidemiology